Identificación de variantes zoonóticas de Cryptosporidium, Blastocystis y Enterocytozoon en terneros de la provincia de Buenos Aires, Argentina - Del Coco, Valeria Fernanda (2016)
Cryptosporidium, Blastocystis, and Enterocytozoon are cosmopolitan microscopic parasites that can cause severe diarrheal disease in humans and animals, and can be lethal in immunocompromised individuals..Cattle can become a major source of infection of those zoonotic agents for humans if the development of the livestock industry is not accompanied by appropriate preventive measures for their manure management. \nDuring the period 2011-2013 a survey of Cryptosporidium, Enterocytozoon bieneusi and Blastocystis was conducted in dairy farms distributed in 12 municipalities of the Cuenca Mar y Sierras, Province of Buenos Aires. Fecal specimens of 209 calves less than 2 months of age were collected and analyzed by molecular methods to identify and molecularly characterize Cryptosporidium, Enterocytozoon bieneusi and Blastocystis .\nA nested PCR protocol for identification of 18S rRNA gene was used for the detection of Cryptosporidium. To detect C. parvum subtypes, a nested PCR for a genetic polymorphic marker ?surface glycoprotein GP60 gene- was used. \nFor E. bieneusi identification, a 400 bp fragment corresponding to the entire region of ITS region and flanking portions of both major and minor subunits rDNA was amplified by nested PCR. To identify Blastocystis, a PCR based on the detection of a fragment of SSU rDNA gene was performed.\nA total of 87 samples were positive for Cryptosporidium (41,62%). Cryptosporidium bovis was detected in a single sample while the rest were all C. parvum. Subtyping of the C. parvum isolates revealed a wide variety of zoonotic subtypes: IIaA16G1R1, IIaA18G1R1, IIaA19G1R1, IIaA20G1R1, IIaA21G1R1, IIaA22G1R1, IIaA23G1R1 were detected. Coinfections were detected in two samples with IIaA22G1R1 and IIaA21G1R1.\nE. bieneusi was detected in 10 samples (4.8%). Six genotypes were found with five of them being previously reported in humans. Genotypes D, I, J and BEB4, previously described in calves and humans, were identified. EbpC, which has been previously described in humans, was found for the first time in calves. A new genotype, BEB10, was identified in a calf. The most prevalent genotype was the J, followed by I. No mixed infections were detected.\nA total of 6 stool samples showed coinfection by Cryptosporidium and E. bieneusi. The following associations were found: C. bovis with genotype J, C. parvum subtype IIaA18G1R1 with genotype I, IIaA20G1R1 with genotype D, IIaA20G1R1 with genotype J, IIaA21G1R1 with genotype BEB4 and IIaA22G1R1 with genotype J. \nBlastocystis was not detected.\nThese results show a wide genetic diversity of C. parvum and E. bieneusi with zoonotic genotypes and subtypes in calves in Buenos Aires province. The presence of these microorganisms in calves suggests that these animals could represent a risk to public health through contamination of drinking water and fresh produce. For a better understanding of zoonotic transmission of these agents it is essential to carry out molecular studies of isolates from humans who live with or are in contact with these animals.